The last-mile challenge: Water, sanitation, and hygiene (WASH) in the Philippines - Valerie Gilbert Ulep; Jann Trizia Talamayan; Lyle Casas; Jon Michael Villase\~nor; Elmira Bacatan (Philippine Institute for Development Studies (PIDS), 2024)
Over the years, the Philippines has made progress in improving water, sanitation, and hygiene (WASH) services. Despite this progress and sustained economic growth, waterborne diseases remain a leading cause of morbidity and hospitalization, particularly among the poorer segments of the population. Further, much still has to be done to achieve universal coverage of safely managed WASH services across all settings-schools, child development centers, health facilities, and households. These disparities contribute to a substantial disease burden driving poor health and nutrition outcomes. Using various secondary data sources, this paper deep dives into the current state of WASH in the Philippines, including its link to nutrition. This paper explores the disease burden associated with WASH, the current conditions of WASH in the Philippines pertaining to both demand and supply factors, and the governance challenges hindering the achievement of universal WASH coverage. Significant disparities in access to WASH persist, particularly among the poorest households in the poorest areas. The last mile challenge in WASH is particularly evident in the poorest regions where even basic water and sanitation services are lacking. This highlights the need to improve services for the vulnerable populations. Bridging these gaps through streamlined governance, efficient resource allocation, and targeted local interventions in underserved areas is vital to achieving universal and equitable access to safe water and sanitation
Keywords: 330; water; sanitation; and hygiene; last-mile challenge; Philippines